Thermomechanischer Kontakt und stochastische Dynamik gleitender Körper mit rauen Oberflächen - Oestringer, Lukas Julian (Schriftenreihe des Instituts für Technische Mechanik, Karlsruher Institut für Technologie, 2023)
Within this work, the friction coefficient is calculated for the dry contact of two sliding metallic bodies as a function of various physical parameters. For this purpose, a thermomechanical model is developed and evaluated for different contact configurations considering the surface roughness of both contact bodies. Subsequent investigations on the consequences of the calculated friction coefficient in the context of friction-induced vibrations are carried out.